Reduced responsiveness of the hypothalamic-pituitary-adrenal axis in Boran (Bos indicus) cattle infected with Trypanosoma congolense - Abebe, G.; Eley, R.M.; Ole-MoiYoi, O.K. (Oxford University Press, 1993)
The response of the pituitary-adrenal axis to corticotrophin-releasing hormone (CRH) and the adrenal response to adrenocorticotrophin hormone (ACTH) stimulation were studied during infection of Boran (Bos indicus) cattle with Trypanosoma congolense. For CRH, 15 animals were challenged during pre-infection and infection phases, while for ACTH 10 animals were challenged during pre-infection, infection and post-treatment phases of the experiments. The axis showed a reduced responsiveness after CRH challenge during patent parasitaemia, manifested by low (p<0.05) plasma ACTH and cortisol concentration as compared to the pre-infection CRH challenge concentrations. Cortisol concentration after ACTH challenge during pre-infection, infection and post-treatment phases did not differ. The reduced pituitary-adrenal response to CRH challenge and the normal adrenal response to ACTH challenge found during trypanosomiasis indicates pituitary dysfunction due to infection.